Relative risks of becoming overweight and obese in children after 6 years in secondary school - Pipop Jirapinyo (2018)
The authors carried out a longitudinal study of bodyweights of secondary-school children from Grade VII to Grade XII. Initial data of weight for height ai Grade VII showed that the prevalences of overweight boys and girls were 13.6% and 9.9% and of obesity of boys and girls 26.8% and 13.5%, respectively. However, when these children were at Grade XII the prevalences of overweight of boys and girls were 14.0% and 10.5% and of obesity of boys and girls were 15.0% and 10.8%, respectively. The relative risks of becoming overweight of boys and girls at Grade XII who were already overweight at Grade VII were 1.5 and 4.0 respectively, and the relative risks of obesity in boys and girls at Grade XII who were already obese at Grade VII were 1.4 and 4.6, respectively. The present study showed that without any nutritional intervention those children, especially girls who were overweight and obese were more likely to maintain their bodyweights throughout the 6-year period in secondary school.